Analisis Optimasi Input Produksi Jagung di Desa Waimangurah, Kecamatan Wewewa Barat, Kabupaten Sumba Barat Daya - MANGNGI, JENETE PRISKILA; AGUNG, I DEWA GEDE; ARTINI, NI WAYAN PUTU (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2017)
Analysis on Input Optimization of Corn Production in Waimangura Village, Sub-District of West Wewewa, Southwest Sumba Regency The purposes of the study were: to determine the influence of factors of productionin corn farming on production and to analyze the level optimum use of productioninputs in the corn farming. The research area was determined purposively. Theanalytical methods used to analyze the production inputs that affect the productionwere a Cobb-Douglass model of Production Function, and marginal product valueanalysis to determine the level of optimization of the use of production inputs. Theresults of the study are as follows: (1) Production inputs used in the corn farming arethe area of land, seed, labor, Urea, NPK fertilizer, M-8 fertilizer, Super ACI fertilizerand fungicides. (2) The use of production inputs in the study area are as follows,Partially, only urea fertilizer significantly affected the corn production, while otherproduction inputs were not significantly affected on the corn farming. (3) The use ofproduction inputs in the study area have not been optimal. For the use of productioninputs of urea, M-8 and Super ACI fertilizers was not optimal. Thus, the use ofproduction inputs need to be added to reach optimal use of production inputs, whileland, labor, seed, NPK fertilizer and fungicides have exceeded the optimal use so thatthe use of inputs should be reduced to gain optimal results.
Keywords: corn farming; production inputs; optimization